Price Competitiveness of International Tourism Destinations and Tourism Demand, Tourism Receipts Relationship - Göral, Ramazan (European Journal of Multidisciplinary Studies, 2016)
The competitiveness of an industry is a critical determinant of how well it performs in world markets. The potential for any country’s tourism industry to develop will depend substantially on its ability to maintain competitive advantage in its delivery of goods and services to visitors. Competitiveness is a general concept that encompasses price differentials coupled with exchange rate movements, productivity levels of various components of the tourist industry and qualitative factors affecting the attractiveness or otherwise of a destination. Given some evidence on the price sensitivity of the demand for travel, destinations need to monitor their price competitiveness relative to alternate locations. Changing costs are among the most important factors influencing the choice of a destination with prices being an essential component in the overall tourism competitiveness of a destination. The aims of this study are; first, to demonstrate the country’s tourism price competitiveness rank; second, examine the relationship between price competitiveness and tourism demand and also with tourism receipts.